Oxybutynin and tolterodine in a trial for treatment of overactive bladder in Iranian women. - Elham Aziminekoo; Zinat Ghanbari; Shahrzad Hashemi; Maryam Nemati; Fedyeh Haghollahi; Nasim Shokuhi (Tehran University of Medical Sciences, 2014)
Objective: To evaluate the efficacy and side effects of Oxybutinin in comparison to tolterodine in treatment of overactive bladder (OAB) with detrussor overactivity (DOA) in Iranian women. Materials and methods: One hundred Iranian old women with clinical symptoms of OAB who show IDO in the filling cystometry participated in this randomized double-blinded parallel-group by using two kinds of the drugs for 4- week course (2 mg tolterodine twice-daily, or oxybutinin 5 mg, three times a day) in alike packages. We collected data from 3-day FVC before and after the treatment course. The effectiveness of each drug was studied using the paired t-test and improvement after treatment between two groups was compared by independent T-test. Results: Positive changes in urinary urgency, Frequency and Urge incontinence after treatment in both groups were seen but mean improvements in the all were larger in the patients who treated by oxybutinin especially in terms of urgency and Urge incontinence. Dry mouth was the most common side-effect in two groups. Unlike other studies it was higher in the tolterodine group but the difference was not significant. Conclusion: Four week treatment with oxybutinin was better than tolterodine in improving urgency and urge incontinence but there were not statistically significance between them.